Building Awareness About Computational Thinking as a Research Field through a Graduate Course for Computer Scientists: a Metacognitive and Self-regulated proposal - Leite, Paula Torales; Guarda, Graziela Ferreira; Silveira, Ismar Frango (Anais do Workshop sobre Educação em Computação (WEI), 2023)
The area of Computational Thinking has been grown the last years and became an important research field that relies on the field of Computer Science at the same time that intersects with different areas like Mathematical Reasoning, Problem Solving and Engineering. Despite the impact and relevance of this area, many professionals on Computer Science and related areas are usually not aware of the Computational Thinking topics as part of a new research area. In this sense, this paper discusses a syllabus proposal for a graduate course on Computational Thinking for Computer Scientists that relies over Metacognition and Self-regulated learning.